2017
DOI: 10.1038/s41467-016-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

CLK-dependent exon recognition and conjoined gene formation revealed with a novel small molecule inhibitor

Abstract: CDC-like kinase phosphorylation of serine/arginine-rich proteins is central to RNA splicing reactions. Yet, the genomic network of CDC-like kinase-dependent RNA processing events remains poorly defined. Here, we explore the connectivity of genomic CDC-like kinase splicing functions by applying graduated, short-exposure, pharmacological CDC-like kinase inhibition using a novel small molecule (T3) with very high potency, selectivity, and cell-based stability. Using RNA-Seq, we define CDC-like kinase-responsive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 62 publications
7
105
0
Order By: Relevance
“…Interestingly, our RNA-Seq data suggested that cellular status of MYC slightly affected the determination of downstream AS events in response to CLK inhibition because T-025 caused similar AS in four tested solid cancer cell lines, including MYC-amplified COLO320HSR cells. The finding that MYC slightly affected CLK inhibitor-dependent AS events was also supported by a previous finding that CLK inhibitor, T3-dependent AS events mostly (~75%) overlapped between the hTERT un-transformed fibroblast cells and MYC-amplified HCT116 colorectal cancer cells (Funnell et al, 2017). We also show that transcriptional regulation of CLK2 and other CLK kinases were independent on MYC activation, degree of T-025-mediated SE was similar regardless MYC induction, and AS events regulated by MYC induction or T-025 rarely overlapped.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Interestingly, our RNA-Seq data suggested that cellular status of MYC slightly affected the determination of downstream AS events in response to CLK inhibition because T-025 caused similar AS in four tested solid cancer cell lines, including MYC-amplified COLO320HSR cells. The finding that MYC slightly affected CLK inhibitor-dependent AS events was also supported by a previous finding that CLK inhibitor, T3-dependent AS events mostly (~75%) overlapped between the hTERT un-transformed fibroblast cells and MYC-amplified HCT116 colorectal cancer cells (Funnell et al, 2017). We also show that transcriptional regulation of CLK2 and other CLK kinases were independent on MYC activation, degree of T-025-mediated SE was similar regardless MYC induction, and AS events regulated by MYC induction or T-025 rarely overlapped.…”
Section: Discussionsupporting
confidence: 81%
“…of three independent experiments ( n = 3). IC 50 values and 95% CI were determined by using Prism. Data information: The chemical structure of T3, the result of enzymatic assay of T3, and AS events modulated by T3 in HCT116 are cited from a previous article (Funnell et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, SRPK family members exhibit highly tissue-specific expression profiles (Nakagawa et al, 2005; Wang et al, SRPKIN-1 (Hatcher et al, 2018) (Figure 1A). In contrast, treatment of mESCs with T3, a selective inhibitor of the closely related CLK kinases (Funnell et al, 2017), which have also been shown to phosphorylate splicing factors (Colwill et al, 1996), leads to near complete inhibition of SR-protein phosphorylation ( Figure 1A). Our results suggest that SRPKs are not the major SRSF protein kinases in mESCs, and may have acquired other developmental function(s) during metazoan evolution.…”
Section: Introductionmentioning
confidence: 95%